Konsep Filsafat Pendidikan Al-Ghozali Dan Relevansinya Dalam Pembelajaran Bahasa Arab - Alfin Sanjaya; Syifa Shofura (Universitas Insan Budi Utomo, 2023)
Education is a systematically designed process aimed at producing significant changes in human behavior, according to Imam Al-Ghazali. In this context, Al-Ghazali believes that the central focus of education is the heart, as the essence of a human being lies within the heart, not in the physical elements but within the heart. He views humans as theocentric and directs the concept of education towards the formation of noble character. This study employs a qualitative method known as library research, involving the exploration of sources from various literature and online journals. The research findings reveal that Al-Ghazali's philosophical concept in education includes knowledge as a process, knowledge as an object, and knowledge grounded in Shariah. The implementation of these educational objectives is evident through the curriculum adopted by the government, particularly emphasizing character development within the framework of the independent curriculum. Al-Ghazali's educational philosophy is rooted in fundamental ethical concepts, notably known as